Bulharská literatura na internetovém portálu iLiteratura.cz - Ivana Srbková (Studia Ethnologica Pragensia, 2016)
The internet literary magazine iLiteratura.cz was built from 2000 to 2002. From different angles it captures and comments the current state of book supply in the Czech Republic and abroad, but at the same time it serves as an extensive archive with more than 8 thousand texts and a valuable source of information for professional and general public. It targets mainly on contemporary literature. As the only one of the Czech literary projects it is dedicated to literatures written in different languages including minority ones. The portal, structured in fourty sections, defined mostly by the language of the particular literature, is a modern alternative to traditional literary and cultural periodicals, it publishes similarly aimed articles. However, it offers them in a different environment and in uncomparably much larger quantities. It focuses on wide audience, the typical reader of iLiteratura.cz is a person with university degree. The chief editor of iLiteratura.cz is the translator, literary journalist and university teacher Jovanka Šotolová. The Bulgarian section „knigi: Bulharsko“, where I work as an editor, started its activity in 2003. The content of the section tries to cover all the reception of Bulgarian literature in our country, the situation in Bulgaria is mapped selectively. The greatest attention has been paid to two important and the most translated contemporary Bulgarian authors Georgi Gospodinov and Alek Popov, from the women authors the novelist and playwright Teodora Dimova is leading, attention is paid also to much younger authors or vice versa classics. Members of ethnic minorities are represented also. The readers meet with great interest also texts from the field of lexicography. In the field of non-fiction the sociological theme about Bulgarian Vojvodovo of Marek Jakoubek and Lenka Jakoubková Budilová has provoked an interest. The Bulgarian section informs through invitations and news about literary prizes, events and festivals. As for articles reviews prevail clearly, next are extracts and writers’ portraits. Among the contributors are represented all ages, but especially young generation to middle age one. If we look at the attendance of the Bulgarian section, undoubtedly Ani Burova’s review „Bulgarian literature during the last fifteen years“ has being led for a long time, but there is a considerable interest in other summarizing texts by other authors. A classic printed yearbook „Literature in the world and in Europe“, which brought articles on literature written in Bulgarian, has become an accompanying action. iLiteratura.cz panel at the International book fair Book World Prague 2005, devoted to Slavonic literatures, also talked about Bulgarian literature.